2022
DOI: 10.3390/antiox11020395
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Responses of Antioxidant and Glyoxalase Systems to Seed Aging Based on Full-Length Transcriptome in Oat (Avena sativa L.)

Abstract: Seed aging is a major challenge for food security, agronomic production, and germplasm conservation, and reactive oxygen species (ROS) and methylglyoxal (MG) are highly involved in the aging process. However, the regulatory mechanisms controlling the abundance of ROS and MG are not well characterized. To characterize dynamic response of antioxidant and glyoxalase systems during seed aging, oat (Avena sativa L.) aged seeds with a range of germination percentages were used to explore physiological parameters, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 79 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…It is indispensable for the earliest metabolic events during seed germination and maintenance of seed vigor [ 14 ]. The level of GSH was suggested to be a promising indicator for seed germination and seedling growth, and was correlated with seed longevity [ 33 , 34 ]. GR is considered to be a crucial enzyme that works on the catalytic reduction of GSSG to the reduced GSH form, thereby involving in plant stress resistance, seed vigor maintenance, growth, and development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is indispensable for the earliest metabolic events during seed germination and maintenance of seed vigor [ 14 ]. The level of GSH was suggested to be a promising indicator for seed germination and seedling growth, and was correlated with seed longevity [ 33 , 34 ]. GR is considered to be a crucial enzyme that works on the catalytic reduction of GSSG to the reduced GSH form, thereby involving in plant stress resistance, seed vigor maintenance, growth, and development.…”
Section: Discussionmentioning
confidence: 99%
“…The deletion of chloroplast specific GR2 leads to the embryo lethality, while lack of mitochondrial GR2 leads to a partially oxidized glutathione pool and decreased seed ageing resistance of Arabidopsis [ 14 , 21 ]. In addition, our previous study found that the expression of GR1 in aged A. sativa seed embryos (aged from 24 d to 42 d) decreased by 50%–70% compared with the control after imbibition for 24 h and that GR2 levels decreased significantly in minorly and moderately aged seeds, but were raised significantly in severely aged seeds [ 33 ]. In present study, the expression of AsGR2-C2 and AsGR2-D decreased significantly in dry seeds after ageing treatment, but they increased rapidly in the early stage of imbibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of the aging or deterioration of oat seeds have been investigated, including changes in antioxidants and gene expression (Kong et al, 2015), as well as mitochondrial structure (Xia et al, 2015). Tricarboxylic acid (TCA) cycle (Chen et al, 2016) and AsA‐GSH cycle are affected due to activity of various enzymes, such as APX, DHAR, MDHAR, and so forth, in medium vigor seeds after aging (Cheng et al, 2020; Sun et al, 2022). The MDA content, CAT and APX activity were maximized in oat seeds after 32 days of artificially accelerated aging, affecting pathways such as the TCA cycle in mitochondria (Cheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the identification and expression analysis of these genes at the whole-genome level will help to rapidly advance stress-resistant breeding and seed vigor improvement in oat. In our previous research, we discovered a close association between the GSH-dependent glyoxalases and the AsA-GSH cycle with oat seed vigor, where GSH content serves as a potential marker for seed germination percentage ( Sun et al., 2022b ). We also conducted a genome-wide identification of the glutathione reductase ( GR ) genes involved in the AsA-GSH cycle and analyzed its expression pattern during seed germination under stress conditions ( Sun et al., 2022a ).…”
Section: Introductionmentioning
confidence: 99%